2018
DOI: 10.1038/sdata.2018.93
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ladybird Henosepilachna vigintioctopunctata transcriptomes across various life stages

Abstract: Henosepilachna vigintioctopunctata is a vegetable pest that has spread worldwide. It belongs to the Coccinellidae family, whose members exhibit remarkable diversity, both in terms of their diets and the colored spots that appear on the elytra in the adult stage. Transcriptomic data from H. vigintioctopunctata at different life stages would be useful for further investigating the genetic basis of this dietary diversity and the formation of the colored spots in ladybird beetles, as well as revealing the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…Moreover, we found that the five white transcripts were detectable from embryo (egg) to adults. In agreement with our result, the five white transcripts were discovered in the transcriptomes from egg, larva, pupa and adult (Zhang et al, 2018). Furthermore, white1, white3, white4 and white5 were highly expressed in the eggs and adults, whereas white2 was abundantly transcribed at the early stage within each instar.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, we found that the five white transcripts were detectable from embryo (egg) to adults. In agreement with our result, the five white transcripts were discovered in the transcriptomes from egg, larva, pupa and adult (Zhang et al, 2018). Furthermore, white1, white3, white4 and white5 were highly expressed in the eggs and adults, whereas white2 was abundantly transcribed at the early stage within each instar.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, five genes encoding ABCG transporters were identified. The five transcripts presented in each of the transcriptomes were obtained from egg, larva, pupa and adult (Zhang et al, 2018) (Table S1).…”
Section: Identification Of White Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome sequencing is an efficient and low-cost method by which to explore gene expression patterns at multiple developmental stages 6,7 , tissues in insects 8,9 . Many insect transcriptomes have been obtained using next-generation sequencing techniques for functional genomic studies 10,11 .…”
Section: Background and Summarymentioning
confidence: 99%